Fast dynamic channel allocation algorithm based on priority channel reservation - SHI Wen-xiao; ZHAO Jun; CHI Xue-fen; LI Na (Tongxin xuebao)
Aiming at overcoming the shortages of the current fast dynamic channel allocation algorithm in TD-SCDMA system,a novel fast dynamic channel allocation algorithm based on priority channel reservation was proposed.This algorithm defined call priority by equipment attribution of baton handover user,reserved channels for baton handover calls.Combining with grouping borrowed algorithm,the algorithm made MB DCA strategy more flexible.Simulation results show that,comparing to the mixed-data rate grouping borrowed algorithm,the proposed algorithm achieves the preferential access of VIP and high rate mobile user,reduces the call failure probability resulted from the baton handover,improves the performance of data service,and increases the channel utilization efficiency.